A REKONSTRUKSI POLA PIKIR BERPENDIDIKAN DALAM KONSEP ILMU PENGETAHUAN Q.S AL-MUJADALAH:11 DAN AZ-ZUMAR: 8-9 - Nabila Nailil Amalia; Asbarin; Siti Aisyah (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2024)
The urgency of becoming an educated person is a way to advance Islamic civilization now and in the future. The aim of this research is to understand the educated mindset in the concept of science Q.S Al-Mujjadi: 11 and Az-Zumar: 8-9. The method used is qualitative research with a literature study approach. The data collection technique used was documentation and descriptive analysis and then conclusions were drawn. The result of this research is that someone who has faith and knowledge will be raised in rank by Allah in accordance with Allah's word in Surah al-Mujjadi verse: 11. In Q.S az-Zumar: 8-9, it is emphasized that there is a difference between people who know and don't know and the nickname ulul albab is someone who can always learn from the events they experience. The value of knowledge contained in Q.S Al-Mujjadi: 11, namely humans as social creatures so they can respect other humans, and in Q.S az-Zumar: 8-9, namely humans as obedient servants of Allah and the Messenger of Allah, there is a change for the better, very fear of Allah's punishment and always hope for Allah's mercy for good deeds of the dhohir nature and others.